2010
DOI: 10.29333/ejgm/82865
|View full text |Cite
|
Sign up to set email alerts
|

Mean Platelet Volume may be Reflects the Disease Activity of Ulcerative Colitis

Abstract: Aim:To determine the relation between the disease activity of ulcerative colitis and mean platelet volume (MPV)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
3
2
1
1
Order By: Relevance
“…The statistically significant declined MPV in CD patients observed in the present study is in accordance with findings of prior studies [9,10], suggesting that MPV may be helpful in clinical practice [34,35]. …”
Section: Discussionsupporting
confidence: 93%
“…The statistically significant declined MPV in CD patients observed in the present study is in accordance with findings of prior studies [9,10], suggesting that MPV may be helpful in clinical practice [34,35]. …”
Section: Discussionsupporting
confidence: 93%
“…On the bases of obtained results MPV indicator can be regarded as a marker of exacerbation of inflammation of colonic mucosa in patients with UC. Güçlü et al research [ 23 ] and our own results confirm that the number of blood platelets increases and the MPV decreases in the active UC. Large platelets “megathrombocytes” (highly reactive cells that are actively involved in the inflammatory response) are gradually consumed to form platelet aggregates and different cell complexes [ 23 24 ].…”
Section: Discussionsupporting
confidence: 83%
“…Güçlü et al research [ 23 ] and our own results confirm that the number of blood platelets increases and the MPV decreases in the active UC. Large platelets “megathrombocytes” (highly reactive cells that are actively involved in the inflammatory response) are gradually consumed to form platelet aggregates and different cell complexes [ 23 24 ]. In addition, activated platelets contribute to the formation of microthrombosis in the intestinal microcirculation.…”
Section: Discussionsupporting
confidence: 83%
“…Yüksel et al [41] UC (61) 27 Reduced MPV in UC compared to HC Inverse correlation between MPV and disease activity Inverse correlation between MPV and disease extent Järemo et al [39] UC (18), 12 Reduced MPV in UC patients compared to HC CD (9) Inverse correlation between MPV and disease activity Güçlü et al [42] UC (41) (-) Reduced MPV in active compared to non-active disease Voudoukis et al [46] UC (91), CD (107) 102 Reduced MPV in IBD patients compared to HC Correlation of MPV with Hb and sTfR Öztürk et al [45] UC (103), CD (72) 40 Reduced MPV in IBD compared to HC MPV decreases after remission in UC MPV increases after remission in CD Kapsoritakis et al [40] UC (93), CD (66) 38 Correlation between MPV and disease activity indices Correlation between MPV and disease extent Kayahan et al [44] UC (37) 20 Correlation between MPV and disease activity indices Reduced MPV in UC compared to HC Liu et al [43] CD ( PLT granular products, such as P-selectin, GP Ⅱb/Ⅲa, CD40L, and GP53, are incorporated into the cytoplasmic membrane, giving them a more adhesive and interacting phenotype. Moreover, PLT during activation develop receptors for chemokines, cytokines, and complement components, enabling them to participate in various inflammatory cascades in IBD [1] (Figure 2).…”
Section: Disease (N ) Hc (N ) Mpv Correlationsmentioning
confidence: 99%
“…In IBD patient studies a MPV value decrease has long been observed [39] which has been inversely correlated with endoscopic and disease activity indices, such as C-reactive protein and erythrocyte sedimentation rate [40][41][42][43][44] . This MPV reduction can be attributed to the decreased circulating reticulated PLT number that was found in patients with active UC compared to inactive and healthy control subjects [44] .…”
Section: Platelet Changes In Ibdmentioning
confidence: 99%